2021
DOI: 10.1038/s41392-021-00701-5
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling in cancers and targeted therapies

Abstract: Wnt/β-catenin signaling has been broadly implicated in human cancers and experimental cancer models of animals. Aberrant activation of Wnt/β-catenin signaling is tightly linked with the increment of prevalence, advancement of malignant progression, development of poor prognostics, and even ascendence of the cancer-associated mortality. Early experimental investigations have proposed the theoretical potential that efficient repression of this signaling might provide promising therapeutic choices in managing var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
160
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(205 citation statements)
references
References 455 publications
1
160
0
Order By: Relevance
“…After reducing the expression level of circPVT1 in PTC cells, the ability of cell proliferation, migration, and invasion were significantly inhibited, and the Wnt/β-catenin signaling pathway was also inhibited. The Wnt/β-catenin signaling pathway, also known as the classic Wnt signaling pathway, has been studied in-depth [ 51 , 52 ]. Activation of the classic Wnt signaling pathway can contribute to extracellular Wnt combining with the transmembrane receptors LRP5/6 and Fzd to form a complex.…”
Section: Discussionmentioning
confidence: 99%
“…After reducing the expression level of circPVT1 in PTC cells, the ability of cell proliferation, migration, and invasion were significantly inhibited, and the Wnt/β-catenin signaling pathway was also inhibited. The Wnt/β-catenin signaling pathway, also known as the classic Wnt signaling pathway, has been studied in-depth [ 51 , 52 ]. Activation of the classic Wnt signaling pathway can contribute to extracellular Wnt combining with the transmembrane receptors LRP5/6 and Fzd to form a complex.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt exerts its effects through three signaling pathways, the most classic being the Wnt/β-catenin signaling pathway, mediated by β-catenin ( 42 ). It has been reported that the abnormal activation of the Wnt/β-catenin signaling pathway is involved in a number of diseases, including cancer, genetic diseases and organ fibrosis, as well as in the occurrence of EMT ( 43 ). Therefore, it was hypothesized that CtBP2, as a transcriptional co-repressor, may interact with TGIF and participate in the development of ESCC through the Wnt/β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical WNT signaling pathway mediated by WNT3A stabilizes β-catenin and leads to its association with the coactivator CBP for transcribing genes related to self-renewal, potency, and proliferation ( 77 ). However, the non-canonical WNT signaling pathway mediated by WNT5A induces the activation of various kinases such as PKC, CaMKII, SIK, AMPK, and MAPK ( 5 , 8 , 79 ). PKC further phosphorylates Ser89 of p300, which increases its affinity for β-catenin ( 77 ).…”
Section: Coactivators Regulating the Output Of The Wnt Signaling Path...mentioning
confidence: 99%
“…The PTB domain of IRS-1 then translocates the β-catenin-IRS-1 complex to the nucleus ( 143 ). β-catenin binding to IRS-1 with its C-terminus may thus prevent phosphorylation at its N-terminus by GSK3β, which primes β-catenin for ubiquitination and degradation ( 8 , 144 ). So, IRS-1, a docking protein for both IGF-1 and insulin receptors, can regulate the subcellular localization and activity of β-catenin in cells that are responsive to the mitogenic action of IGF-1 ( 142 , 145 ).…”
Section: Kinases Regulating the Activity Of β-Cateninmentioning
confidence: 99%